The Influence Of Reproductive Health Education Through Small Group Discussion Method With Knowledge Of Sexual Abuse In Early Adolescence ( At SMP Negeri 1 Grabagan) Tuban Regency ) - Damayanti, Tri Yunita Fitria; Astutik (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2024)
Sexual violence against children is increasingly common and is becoming global in almost all countries. Cases of sexual violence against children continue to increase from time to time. This increase is not only in terms of quantity or number of cases that occur, but also in terms of quality. The aim of the research is to determine the influence of reproductive health education through the small group discussion method with knowledge about sexual abuse in early adolescents at SMPN 1 Grabagan Tuban. This research used pre-experimental (One group pre-post test design). The sampling method used simple random sampling technique with a sample size of 44 respondents. The instruments used were SOPs and questionnaire sheets. Data analysis used the Wilcoxon test. The research results showed that knowledge about sexual abuse among female students at SMPN 1 before being treated was in the medium category at 30 (68.2). Based on analysis using SPSS For Windows with the Wilcoxon signed ranks test with a significance level of α = 0.05, the result was Asymp.Sig (2-tailed) = 0.000 < 0.05, it was concluded that H1 was accepted, meaning that there was an influence of Reproductive Health Education Through the Small Group Discussion Method with Knowledge about Sexual Abuse in Early Adolescents (At Smp Negeri 1 Grabagan, Tuban Regency). Based on these results, it can be concluded that the influence of reproductive health education using the Small Group Discussion method can increase knowledge about sexual abuse in early adolescents at SMP Negeri 1 Grabagan, Tuban Regency.